A prospective study of 138 arthroscopies of the temporomandibular joint - Silva,Paulo Alexandre da (2015)
INTRODUCTION: Internal derangements (ID) of the temporomandibular joint (TMJ) have a multifactorial etiology and are most often treated conservatively by splints, physical therapy and medications. Only in 2-5% of cases are the treatment surgical, either by arthroscopy or arthrotomy.OBJECTIVE: To evaluate improvement of mouth opening, pain relief during function, position of the articular disk and complications following Arthroscopic Lyse and Lavage (ALL).METHODS: A prospective study of 78 patients (138 TMJs) with TMJ ID, 5 males and 73 females, mean age 29.7 years, treated between January 2010 and April 2013, who were refractory to conservative treatment, had limited mouth opening and pain localized to the TMJ during function, and who were submitted to TMJ ALL and followed for a period of 12 months, with periodic reviews.RESULTS: ALL was effective in 93.6% of cases, with 85.3% experiencing improvement in mouth opening and 91.2% in pain reduction during function, 63% improvement in disk position and a rate of complications of 6.2%.CONCLUSION: In this study the ALL exhibited a high rate of success with low morbidity in internal derangements of the TMJ.